Visualization and Quantification of the Oral Hygiene Effects of Brushing, Dentifrice Use, and Brush Wear Using a Tooth Brushing Simulator - Ledder, Ruth G.; Latimer, Joe; Forbes, Sarah; Penney, Jodie L.; Sreenivasan, Prem K.; McBain, Andrew J. (Frontiers in Public Health, 2019)
Approaches that reproduce dental hygiene regimens under controlled conditions have applications in preclinical research. We have applied standardized, reproducible brushing regimes to typodonts coated in simulated or biological plaques to assess the effects on tooth cleaning of toothbrush/dentifrice regimens. Replicated typodonts were coated with OccludeTM or GlogermTM indicators to simulate plaque, and brushed reproducibly using a mechanical brushing simulator to compare the cleaning of occlusal surfaces before and after brushing with water or a dentifrice. An in vitro model using salivary inocula to cultivate oral biofilms on typodont surfaces was then developed to evaluate removal of disclosed plaque by new toothbrushes in comparison to toothbrushes with wear equivalent to 3 months of use. Analyses of typodonts brushed under controlled conditions significantly (p < 0.01) distinguished between brushed and unbrushed surfaces and between the use of water vs. dentifrice for the removal of simulated interproximal plaque (p < 0.05). New toothbrushes removed significantly (p < 0.05) more biological plaque from typodont surfaces than brushes that had been worn by repeated brushing. Through controlled and defined brushing of typodonts with simulated and biological plaques, the effectiveness of dental hygiene regimens was compared under reproducible conditions. Data indicate that the cleaning effectiveness of brushing was augmented by the addition of dentifrice and that new brushes were significantly more effective than brushes with substantial wear from previous use. Whilst we have focussed on the occlusal surfaces of molars and worn brushes, the method could be applied to a range of other tooth surfaces and oral hygiene regimens.